BULBOPHYLLUM TRINERVOSUM, A NEW SPECIES OF SECTION MACROCAULIA (ORCHIDACEAE: BULBOPHYLLINAE) FROM WEST JAVA, INDONESIA - Malcolm Victoriano; Yuda Rehata Yudistira (Reinwardtia, 2020)
VICTORIANO, M. & YUDISTIRA, Y. R. 2020. Bulbophyllum trinervosum, a new species of section Macrocaulia (Orchidaceae: Bulbophyllinae) from West Java, Indonesia. Reinwardtia 19(1): 67‒73. ‒‒ A new species of Bulbophyllum (Orchidaceae: Bulbophyllinae) in section Macrocaulia from West Java, Indonesia is described as Bulbophyllum trinervosum Victoriano & Y.R.Yudistira spec. nov. This miniature orchid is found around Cakrabuana mountain range at an elevation of 1,300–1,550 m. The key characteristic of this species is unique among section Macrocaulia in having three nerves on its median sepal instead of five like the other species in this section.